'Schismo‐urbanism': cities, natural disaster, and urban sociology. Issue 3 (18th April 2013) - Kammerbauer, Mark
<x xml:space="preserve">Abstract</x> This paper examines a city and a natural disaster, specifically New Orleans, Louisiana, after Hurricane Katrina of August 2005. Recovery here is ongoing and the process of return is incomplete, with long‐term dislocation to other cities in the United States, such as Houston, Texas. The question arises as to how planning and stratification influence evacuation and return/dislocation and how they result in a particular practice of adaptation. This interrelated process is conceptually integrated and termed 'schismo‐urbanism' and is analysed within a multidimensional theoretical framework to evaluate aspects of urban sociology and natural disasters. Empirical research is based on a quantitative and qualitative mixed‐method case study. Data were collected during two rounds of field research in New Orleans and Houston in 2007 and 2009. As a comparative socio‐spatial study of affected and receptor communities, it makes a novel theoretical and methodological contribution to research on urban disasters in the context of continuing and rapid social change, and is targeted at disaster researchers, planning theorists and practitioners, and urbanists.